Effect of Hematoma Block Combined with Intravenous Diazepam versus Hematoma Block in Closed Colles’ Fracture - Woranuch, MD, Arun; Pinyo, MD, Thanakorn; Sangkomkamhang, MD , Thananit (Journal of Southeast Asian Orthopaedics, 2022)
Introduction: There are many different anesthesia options to reduce pain in reduction of Colles’fracture. The most convenient anesthesia option is a hematoma block but this procedure is not a good anesthesia because patients still experience moderate pain during reduction. From current observational studies show that hematoma block added through intravenous sedation can reduce pain in patients. Objective: To compare the effectiveness of the hematoma block with intravenous (IV) diazepam versus hematoma block alone in relieving pain of the closed reduction of Colles’ fracture in adult patients. Materials and Methods: Closed Colles’ fracture patients who visited emergency department, Khon Kaen hospital during December 2016-December 2017 and were performed close reduction were enrolled to the study and were randomly assigned to hematoma block combined with intravenous diazepam group and hematoma block group. Visual analog scale (VAS) before and during the procedure were evaluated in both groups. The primary outcome was the mean difference of visual analog scale. Results: A total of 22 patients were enrolled in the study, 11 patients received hematoma block with IV diazepam and 11 received hematoma block alone. The average VAS scale during reduction was 3.09 for the hematoma block with IV diazepam group and 2.82 for the hematoma block alone group, with a mean difference of 0.27(-1.25-0.71) (p=0.28). No complications were experienced in both trial groups. Conclusion: The effectiveness of hematoma block alone is not difference to hematoma block with IV diazepam to reduce pain during closed reduction in closed Colles’ fracture.